Modified epoxy resin adhesive and preparation method thereof

By introducing modified toughening agent and nanodiamond/boron nitride@PDA composite materials into epoxy resin glue, the problems of brittle quality and poor wear resistance of epoxy resin glue are solved, and higher toughness and resistance are achieved Grinding and high temperature resistance extend the service life and improve bonding strength.

CN119242234AInactive Publication Date: 2025-01-03DONGGUAN YUANBANG ELECTRONIC MATERIALS CO LTD

Patent Information

Application Number
CN202411433159.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The brittle quality, low toughness and poor wear resistance of pure epoxy resin glue limit its application in high-tech and high-demand fields.

Method used

Using modified toughening agent and nanodiamond/boron nitride@PDA composite material, the polyp-phenylene ether sulfone and itaconic anhydride in the modified toughening agent form a carbamate bond, and combines nanodiamond/boron nitride@ PDA's high-performance hard filler enhances the toughness and wear resistance of epoxy resin glue.

Benefits of technology

It significantly improves the toughness, wear resistance and high temperature resistance of epoxy resin glue, extends the service life of the material, and enhances the bonding strength and electrical insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a modified epoxy resin adhesive and a preparation method thereof, and belongs to the technical field of high polymer materials. The modified epoxy resin adhesive comprises the following components in parts by weight: 90-120 parts of epoxy resin, 8-25 parts of a curing agent, 1-3 parts of a diluent, 0.5-5 parts of a curing accelerator, 4-18 parts of graphite, 1-4 parts of a modified flexibilizer and 10-30 parts of nano diamond / boron nitride (PDA), a polyurethane single soft and hard segment structure and a high-temperature-resistant oxazolidinone ring in the modified toughening agent cooperate with poly (p-phenylene ether sulfone) resin, so that the toughness is effectively enhanced, and crack propagation is inhibited; boron nitride is modified by nano-diamond, wear resistance is optimized, good electric insulativity and chemical corrosion resistance are given to a matrix, polydopamine can promote a compound to be evenly dispersed in the epoxy resin matrix, wear resistance and adhesive force are improved, and the prepared modified epoxy resin adhesive has good toughening and wear-resisting effects and also has the advantages of being good in toughness, good in toughness and good in wear resistance. And the cable also has excellent high temperature resistance, corrosion resistance and electric insulation effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a modified epoxy resin adhesive and a preparation method thereof. Background Art

[0002] Epoxy resin glue is an engineering adhesive made of epoxy resin base, curing agent, diluent, accelerator and filler. Due to its excellent bonding performance, good functionality, relatively low price and simple bonding process, it has been widely used in home appliances, automobiles, water conservancy and transportation, electronic appliances and aerospace industries in recent decades.

[0003] However, with the continuous advancement of science and technology and the development needs of the industry, the limitations of pure epoxy resin glue have gradually emerged, such as brittleness, low toughness and poor wear resistance, which limit its application. The hardness of the cured epoxy resin is enhanced due to the highly cross-linked three-dimensional network structure, which leads to stress concentration and becomes very brittle and hard. In addition, although epoxy resin glue has certain wear resistance, with the increase in actual application needs, the wear resistance of epoxy resin glue itself no longer meets the demand. Therefore, modifying these deficiencies to expand the application field of epoxy resin glue has become an important direction for the current development of the industry. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a modified epoxy resin adhesive and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A modified epoxy resin adhesive comprises the following raw materials in parts by weight: 90-120 parts of epoxy resin, 8-25 parts of curing agent, 1-3 parts of diluent, 0.5-5 parts of curing accelerator, 4-18 parts of graphite, 1-4 parts of modified toughening agent, and 10-30 parts of nano-diamond / boron nitride@PDA; The curing agent is 4,4'-diaminodiphenylmethane; The diluent is butyl glycidyl ether; The curing accelerator is 2-methylimidazole.

[0006] The modified toughening agent is prepared by the following method: Step A1: 4-chloro-6-methyl-m-phenyl diisocyanate, thiohydroxylamine, acetone and triethylamine were mixed, stirred at room temperature for 2-3 hours, rotary evaporated, washed, dried, and itaconic anhydride and methanol were added under nitrogen protection and mixed evenly, the pH was adjusted to 8-9, and the reaction was carried out for 4 hours to obtain an intermediate; Further, the usage ratio of 4-chloro-6-methyl-m-phenyl diisocyanate, thiohydroxylamine, acetone, triethylamine, itaconic anhydride, and methanol is 0.5-1.2 g: 1.85 g: 20 mL: 0.5-0.6 mL: 1-2.5 g: 10-20 mL; Step A2: dehydrating the poly(p-phenylene ether sulfone) and subjecting it to vacuum treatment at 110° C. for 2 h, then lowering the temperature to 60° C., adding toluene and the intermediate under nitrogen protection, and reacting at 80° C. for 2 h to obtain a prepolymer; Further, the amount ratio of poly (p-phenylene ether sulfone), toluene, and the intermediate is 1-1.5g: 20-40mL: 2-2.6g; Step A3: uniformly mix the prepolymer, ethylene glycol diglycidyl ether and 2-ethyl-4-methylimidazole, heat the reaction system to 160° C., and stir the reaction for 2 hours to obtain a modified toughening agent; Furthermore, the usage ratio of the prepolymer, ethylene glycol diglycidyl ether and 2-ethyl-4-methylimidazole is 2.06-5.01 g: 2 mol: 0.04-0.14 g.

[0007] The nanodiamond / boron nitride@PDA is prepared by the following method: Step B1: Concentrated sulfuric acid, concentrated nitric acid and nano-diamonds are mixed, heated in a water bath at 75°C and stirred for 24 hours to obtain pretreated nano-diamonds; then boron nitride is dispersed in NaOH and stirred for 12 hours, 3-aminopropyltriethoxysilane and ethanol are added and mixed, the pH is adjusted to 5, magnetic suspension is stirred at 65°C for 8 hours, and then the pretreated nano-diamonds are added, ultrasonically treated for 2 hours, washed and dried to obtain a diamond / boron nitride composite; Further, the usage ratio of concentrated sulfuric acid, concentrated nitric acid, nanodiamond, boron nitride, NaOH, 3-aminopropyltriethoxysilane, and ethanol is 10.6-12 mL: 3.5-4 mL: 5-9 g: 6-8 g: 12-16 g: 0.2 mL: 3.2-3.8 mL; Step B2: diamond / boron nitride composite, tris(hydroxymethyl)aminomethane) and deionized water were mixed, the pH was adjusted to 8.5, dopamine hydrochloride was added, ultrasonic treatment was performed for 30 min, stirring was performed at room temperature for 24 h, vacuum filtration and washing were performed, and vacuum drying was performed at 60° C. for 24 h to obtain nano-diamond / boron nitride@PDA; Furthermore, the usage ratio of the diamond / boron nitride composite, tris(hydroxymethyl)aminomethane, deionized water, and dopamine hydrochloride is 6-8 g: 5-10 g: 500-900 mL: 2.4 g.

[0008] A method for preparing a modified epoxy resin adhesive comprises the following steps: S1: Weigh epoxy resin, curing agent, diluent, curing accelerator, graphite, modified toughening agent, and nano-diamond / boron nitride@PDA in parts by weight and mix them at room temperature and pressure to obtain a mixed material; S2: putting the mixed material into a high-speed mixer to stir and prepare glue, the speed is 500-1000r / min, and the glue is scraped synchronously with the rotation of the stirring plate to obtain glue liquid; S3: The above glue liquid is sanded for 3-4 hours to obtain modified epoxy resin glue.

[0009] Beneficial effects of the present invention: The modified toughening agent prepared by the invention firstly utilizes the chlorine of 4-chloro-6-methyl metaphenyl diisocyanate and the amino group of thiohydroxylamine to react under the catalysis of acetone and triethylamine, and then utilizes the mercapto group to react with the carbon-carbon double bond of itaconic anhydride to generate an intermediate; secondly, utilizes the hydroxyl group of poly(p-phenylene ether sulfone) to react with the isocyanate group of the intermediate to form a carbamate bond, thereby preparing a prepolymer; finally, utilizes the epoxy group of ethylene glycol diglycidyl ether and the isocyanate group at the end of the prepolymer to perform addition polymerization under the catalysis of 2-ethyl-4-methylimidazole to form an oxazolidinone group, thereby synthesizing the modified toughening agent. In the modified toughening agent, poly(p-phenylene ether sulfone) hydroxyl group and isocyanate group form polyurethane. Due to the unique soft and hard segment structure of polyurethane, it has both the high strength of plastic and the high elasticity of rubber. After being introduced into the epoxy resin network, it effectively improves its high crosslinking density, high brittleness and weak impact resistance, and its toughness is significantly improved. At the same time, the five-membered ring structure of oxazolidinone has a high thermal decomposition temperature, large cohesive energy, and strong carbon-oxygen double bond energy. After being integrated into the epoxy resin, it gives it excellent high temperature resistance. In addition, poly(p-phenylene ether sulfone), as a high-performance thermoplastic resin, has excellent toughness and heat resistance, which can reduce the thermal expansion coefficient, curing shrinkage and internal stress of epoxy resin, effectively inhibit crack propagation, enhance bonding strength, and further improve toughness. In addition, the introduced itaconic anhydride can form crosslinks with the epoxy resin, while enhancing the toughness of the epoxy resin, maintaining its thermal stability, and improving the tensile strength and bending strength, thereby improving the comprehensive performance of the epoxy resin glue. ‌‌ The nano-diamond / boron nitride @PDA prepared by the present invention comprises the following steps: firstly, using acid-washed nano-diamond to prepare pre-treated nano-diamond with carboxyl groups on the surface; then, using boron nitride to react with a silane coupling agent to make its surface contain amino groups; then, using the amino groups on its surface to react with the carboxyl groups of the pre-treated nano-diamond to prepare a diamond / boron nitride composite; and secondly, using dopamine hydrochloride to self-polymerize on the surface of the nano-diamond / boron nitride composite to generate polydopamine to prepare the nano-diamond / boron nitride @PDA. Nanodiamond and boron nitride are used as high-performance hard fillers. Nanodiamond is modified on boron nitride to form a composite material. It can not only work synergistically to optimize surface integrity, reduce local damage during wear, and enhance the wear resistance of epoxy resin glue, but also make the matrix have good electrical insulation and chemical corrosion resistance. At the same time, polydopamine itself has excellent dispersibility, which can promote the uniform dispersion of diamond / boron nitride composites in the epoxy resin matrix, effectively avoiding the agglomeration and phase separation problems of nanofillers, and further strengthening the interfacial bonding between the filler and the resin matrix, thereby improving the overall wear resistance. In addition, polydopamine has excellent adhesion properties, which can further improve the adhesion of epoxy resin glue and avoid peeling, debonding and cracking caused in different environments.

[0010] The modified epoxy resin adhesive prepared by the present invention not only has a good toughening effect and reduces brittleness, but also has excellent wear resistance and corrosion resistance, and prolongs the service life of the material. The modified epoxy resin adhesive has a higher bonding strength and can better firmly bond different materials, which is of great significance for application scenarios requiring high-strength bonding. DETAILED DESCRIPTION

[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0012] A method for preparing a modified epoxy resin adhesive comprises the following steps: S1: Weigh the raw materials by weight, including 90 parts of epoxy resin, 8 parts of curing agent, 1 part of diluent, 0.5 parts of curing accelerator, 4 parts of graphite, 1 part of modified toughening agent (prepared in this embodiment), and 10 parts of nano-diamond / boron nitride @PDA (prepared in this embodiment), and mix the epoxy resin, 4,4'-diaminodiphenylmethane, butyl glycidyl ether, 2-methylimidazole, graphite, modified toughening agent, and nano-diamond / boron nitride @PDA at room temperature and pressure to obtain a mixed material; S2: Put the mixed material into a high-speed mixer to stir and prepare glue at a speed of 500 r / min, and scrape the glue synchronously with the rotation of the stirring plate to obtain glue liquid; S3: grinding the above glue liquid with a sand grinder for 3-4 hours to obtain modified epoxy resin glue; The modified toughening agent is prepared by the following method: Step A1: 0.5 g of 4-chloro-6-methyl-m-phenyl diisocyanate, 1.85 g of thiohydroxylamine, 20 mL of acetone and 0.5 mL of triethylamine were mixed, stirred at room temperature for 2-3 h, rotary evaporated, washed, dried, and 1 g of itaconic anhydride and 10 mL of methanol were added under nitrogen protection and mixed evenly, the pH was adjusted to 8-9, and the reaction was carried out for 4 h to obtain an intermediate; Step A2: dehydrating 1 g of poly(p-phenylene ether sulfone) and evacuating under reduced pressure at 110° C. for 2 h, then lowering the temperature to 60° C., adding 20 mL of toluene and 2 g of the intermediate under nitrogen protection, and reacting at 80° C. for 2 h to obtain a prepolymer; Step A3: 2.06 g of prepolymer, 2 mol of ethylene glycol diglycidyl ether and 0.04 g of 2-ethyl-4-methylimidazole were uniformly mixed, and the reaction system was heated to 160° C. and stirred for reaction for 2 h to obtain a modified toughening agent; The nanodiamond / boron nitride@PDA is prepared by the following method: Step B1: 10.6 mL of concentrated sulfuric acid, 3.5 mL of concentrated nitric acid and 5 g of nano-diamond were mixed, heated in a water bath at 75°C with stirring for 24 h to obtain pretreated nano-diamond; 6 g of boron nitride was dispersed in 12 g of NaOH and stirred for 12 h, 0.2 mL of 3-aminopropyltriethoxysilane and 3.2 mL of ethanol were added and mixed, the pH was adjusted to 5, magnetic suspension was stirred at 65°C for 8 h, the pretreated nano-diamond was added, ultrasonic treatment was performed for 2 h, washing and drying were performed to obtain a diamond / boron nitride composite; Step B2: Mix 6 g of diamond / boron nitride complex, 5 g of tris(hydroxymethyl)aminomethane) and 500 mL of deionized water, adjust the pH to 8.5, add 2.4 g of dopamine hydrochloride, ultrasonically treat for 30 min, stir at room temperature for 24 h, vacuum filter, wash, and vacuum dry at 60 ° C for 24 h to obtain nanodiamond / boron nitride @PDA. Example

[0013] A method for preparing a modified epoxy resin adhesive comprises the following steps: S1: Weigh the raw materials by weight, including 105 parts of epoxy resin, 16 parts of curing agent, 2 parts of diluent, 3 parts of curing accelerator, 11 parts of graphite, 2.5 parts of modified toughening agent (prepared in this embodiment), and 20 parts of nano-diamond / boron nitride @PDA (prepared in this embodiment), and mix the epoxy resin, 4,4'-diaminodiphenylmethane, butyl glycidyl ether, 2-methylimidazole, graphite, modified toughening agent, and nano-diamond / boron nitride @PDA at room temperature and pressure to obtain a mixed material; S2: Put the mixed material into a high-speed mixer to stir and prepare glue, the speed is 750r / min, and the glue is scraped synchronously with the rotation of the stirring plate to obtain glue liquid; S3: grinding the above glue liquid with a sand grinder for 3-4 hours to obtain modified epoxy resin glue; The modified toughening agent is prepared by the following method: Step A1: 0.85 g of 4-chloro-6-methyl-m-phenyl diisocyanate, 1.85 g of thiohydroxylamine, 20 mL of acetone and 0.55 mL of triethylamine were mixed, stirred at room temperature for 2-3 h, rotary evaporated, washed, dried, and 1.75 g of itaconic anhydride and 15 mL of methanol were added under nitrogen protection and mixed evenly, the pH was adjusted to 8-9, and the reaction was carried out for 4 h to obtain an intermediate; Step A2: 1.25 g of poly(p-phenylene ether sulfone) was dehydrated and vacuumed at 110° C. for 2 h, then the temperature was lowered to 60° C., 30 mL of toluene and 2.3 g of the intermediate were added under nitrogen protection, and the mixture was reacted at 80° C. for 2 h to obtain a prepolymer; Step A3: 3.52 g of prepolymer, 2 mol of ethylene glycol diglycidyl ether and 0.09 g of 2-ethyl-4-methylimidazole were uniformly mixed, and the reaction system was heated to 160° C. and stirred for reaction for 2 h to obtain a modified toughening agent; The nanodiamond / boron nitride@PDA is prepared by the following method: Step B1: 11.2 mL of concentrated sulfuric acid, 3.75 mL of concentrated nitric acid and 7 g of nano-diamond were mixed, heated in a water bath at 75°C with stirring for 24 h to obtain pretreated nano-diamond; 7 g of boron nitride was dispersed in 14 g of NaOH and stirred for 12 h, 0.2 mL of 3-aminopropyltriethoxysilane and 3.5 mL of ethanol were added and mixed, the pH was adjusted to 5, magnetic suspension was stirred at 65°C for 8 h, the pretreated nano-diamond was added, ultrasonic treatment was performed for 2 h, washing and drying were performed to obtain a diamond / boron nitride composite; Step B2: Mix 7 g of diamond / boron nitride composite, 7 g of tris(hydroxymethyl)aminomethane) and 700 mL of deionized water, adjust the pH to 8.5, add 2.4 g of dopamine hydrochloride, ultrasonically treat for 30 min, stir at room temperature for 24 h, vacuum filter, wash, and vacuum dry at 60 ° C for 24 h to obtain nanodiamond / boron nitride @PDA. Example

[0014] A method for preparing a modified epoxy resin adhesive comprises the following steps: S1: Weigh the raw materials by weight, including 120 parts of epoxy resin, 25 parts of curing agent, 3 parts of diluent, 5 parts of curing accelerator, 18 parts of graphite, 4 parts of modified toughening agent (prepared in this embodiment), and 30 parts of nano-diamond / boron nitride @PDA (prepared in this embodiment), and mix the epoxy resin, 4,4'-diaminodiphenylmethane, butyl glycidyl ether, 2-methylimidazole, graphite, modified toughening agent, and nano-diamond / boron nitride @PDA at room temperature and pressure to obtain a mixed material; S2: putting the mixed material into a high-speed mixer to stir and prepare glue, the speed is 1000r / min, and the glue is scraped synchronously with the rotation of the stirring plate to obtain glue liquid; S3: grinding the above glue liquid with a sand grinder for 3-4 hours to obtain modified epoxy resin glue; The modified toughening agent is prepared by the following method: Step A1: 1.2 g 4-chloro-6-methyl-m-phenyl diisocyanate, 1.85 g thiohydroxylamine, 20 mL acetone and 0.6 mL triethylamine were mixed, stirred at room temperature for 2-3 h, rotary evaporated, washed, dried, and 2.5 g itaconic anhydride and 20 mL methanol were added under nitrogen protection and mixed evenly, the pH was adjusted to 8-9, and the reaction was carried out for 4 h to obtain an intermediate; Step A2: 1.5 g of poly(p-phenylene ether sulfone) was dehydrated and vacuumed at 110° C. for 2 h, then the temperature was lowered to 60° C., 40 mL of toluene and 2.6 g of the intermediate were added under nitrogen protection, and the mixture was reacted at 80° C. for 2 h to obtain a prepolymer; Step A3: 5.01 g of prepolymer, 2 mol of ethylene glycol diglycidyl ether and 0.14 g of 2-ethyl-4-methylimidazole were uniformly mixed, and the reaction system was heated to 160° C. and stirred for reaction for 2 h to obtain a modified toughening agent; The nanodiamond / boron nitride@PDA is prepared by the following method: Step B1: 12 mL of concentrated sulfuric acid, 4 mL of concentrated nitric acid and 9 g of nano-diamond were mixed, heated in a water bath at 75°C with stirring for 24 h to obtain pretreated nano-diamond; 8 g of boron nitride was dispersed in 16 g of NaOH and stirred for 12 h, 0.2 mL of 3-aminopropyltriethoxysilane and 3.8 mL of ethanol were added and mixed, the pH was adjusted to 5, magnetic suspension was stirred at 65°C for 8 h, the pretreated nano-diamond was added, ultrasonic treatment was performed for 2 h, washing and drying were performed to obtain a diamond / boron nitride composite; Step B2: 8 g of diamond / boron nitride composite, 10 g of tris(hydroxymethyl)aminomethane) and 500-900 mL of deionized water were mixed, the pH was adjusted to 8.5, 2.4 g of dopamine hydrochloride was added, ultrasonic treatment was performed for 30 min, stirring was performed at room temperature for 24 h, vacuum filtration and washing were performed, and vacuum drying was performed at 60° C. for 24 h to obtain nano-diamond / boron nitride@PDA.

[0015] Comparative Example 1 This comparative example is a modified epoxy resin adhesive, which differs from Example 3 in that the modified toughening agent prepared in Example 3 is an equal amount of polybutadiene, and the rest are the same.

[0016] Comparative Example 2 This comparative example is a modified epoxy resin adhesive, which differs from Example 3 in that an equal amount of quartz powder is used to replace the wear-resistant filler prepared in Example 3, and the rest are the same.

[0017] Performance test: The modified epoxy resin glue prepared in Examples 1-3 and Comparative Examples 1-2 was made into a standard test size, and the tensile strength was tested according to GB / T1040.1-2006, the bending test was performed according to GB1042-79, the friction and wear test was performed according to GB3960-83 (the smaller the value of the wear index, the better the wear resistance), the peel strength test was performed according to ASTM D6862-11, and the dielectric constant and chemical corrosion resistance time were tested; the test results are shown in the following table:

[0018] It can be seen from the test data in the table that the modified epoxy resin glue prepared in Example 1 not only has a good toughening effect and reduces brittleness, but also has excellent wear resistance and extends the service life of the material. It can also be seen from the above table that the modified epoxy resin glue prepared by the present invention has excellent high temperature resistance, corrosion resistance and electrical insulation effects, thereby improving the comprehensive performance of the modified epoxy resin glue.

[0019] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a modified epoxy resin adhesive, characterized in that: The following steps are involved: S1: mixing epoxy resin, curing agent, diluent, curing accelerator, graphite, modified toughening agent, and nano-diamond / boron nitride@PDA at room temperature and pressure to obtain a mixed material; S2: putting the mixed material into a high-speed mixer to stir and prepare glue, the speed is 500-1000r / min, and the glue is scraped synchronously with the rotation of the stirring plate to obtain glue liquid; S3: The above glue liquid is sanded for 3-4 hours to obtain modified epoxy resin glue.

2. The method for preparing a modified epoxy resin adhesive according to claim 1, characterized in that: The modified toughening agent is prepared by the following method: Step A1: 4-chloro-6-methyl-m-phenyl diisocyanate, thiohydroxylamine, acetone and triethylamine were mixed, stirred at room temperature for 2-3 hours, rotary evaporated, washed, dried, and itaconic anhydride and methanol were added under nitrogen protection and mixed evenly, the pH was adjusted to 8-9, and the reaction was carried out for 4 hours to obtain an intermediate; Step A2: dehydrating the poly(p-phenylene ether sulfone) and subjecting it to vacuum treatment at 110° C. for 2 h, then lowering the temperature to 60° C., adding toluene and the intermediate under nitrogen protection, and reacting at 80° C. for 2 h to obtain a prepolymer; Step A3: The prepolymer, ethylene glycol diglycidyl ether and 2-ethyl-4-methylimidazole are mixed evenly, and then the reaction system is heated to 160° C. and stirred for reaction for 2 hours to obtain a modified toughening agent.

3. The method for preparing a modified epoxy resin adhesive according to claim 2, characterized in that: Further in step A1, the usage ratio of 4-chloro-6-methyl-m-phenyl diisocyanate, thiohydroxyamine, acetone, triethylamine, itaconic anhydride and methanol is 0.5-1.2 g: 1.85 g: 20 mL: 0.5-0.6 mL: 1-2.5 g: 10-20 mL.

4. The method for preparing a modified epoxy resin adhesive according to claim 2, characterized in that: In step A2, the usage ratio of poly(p-phenylene ether sulfone), toluene and intermediate is 1-1.5 g: 20-40 mL: 2-2.6 g.

5. The method for preparing a modified epoxy resin adhesive according to claim 2, characterized in that: In step A3, the usage ratio of prepolymer, ethylene glycol diglycidyl ether and 2-ethyl-4-methylimidazole is 2.06-5.01 g: 2 mol: 0.04-0.14 g.

6. The method for preparing a modified epoxy resin adhesive according to claim 1, characterized in that: The nanodiamond / boron nitride@PDA is prepared by the following method: Step B1: Concentrated sulfuric acid, concentrated nitric acid and nano-diamonds are mixed, heated in a water bath at 75°C and stirred for 24 hours to obtain pretreated nano-diamonds; then boron nitride is dispersed in NaOH and stirred for 12 hours, 3-aminopropyltriethoxysilane and ethanol are added and mixed, the pH is adjusted to 5, magnetic suspension is stirred at 65°C for 8 hours, and then the pretreated nano-diamonds are added, ultrasonically treated for 2 hours, washed and dried to obtain a diamond / boron nitride composite; Step B2: Mix the diamond / boron nitride complex, tris(hydroxymethylaminomethane) and deionized water, adjust the pH to 8.5, add dopamine hydrochloride, ultrasonically treat for 30 minutes, stir at room temperature for 24 hours, vacuum filter, wash, and vacuum dry at 60°C for 24 hours to obtain nanodiamond / boron nitride@PDA.

7. The method for preparing a modified epoxy resin adhesive according to claim 6, characterized in that: In step B1, the usage ratio of concentrated sulfuric acid, concentrated nitric acid, nanodiamond, boron nitride, NaOH, 3-aminopropyltriethoxysilane and ethanol is 10.6-12 mL: 3.5-4 mL: 5-9 g: 6-8 g: 12-16 g: 0.2 mL: 3.2-3.8 mL.

8. The method for preparing a modified epoxy resin adhesive according to claim 6, characterized in that: In step B2, the usage ratio of diamond / boron nitride composite, tris(hydroxymethyl)aminomethane, deionized water and dopamine hydrochloride is 6-8 g: 5-10 g: 500-900 mL: 2.4 g.

9. The method for preparing a modified epoxy resin adhesive according to claim 1, characterized in that: The curing agent is 4,4'-diaminodiphenylmethane, the diluent is butyl glycidyl ether, and the curing accelerator is 2-methylimidazole.

10. A modified epoxy resin adhesive, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Low temperature curable bottom filling adhesive with heat transfer function and preparation method thereof

    CN106753143A

  • Preparation method of nano-diamond / boron nitride composite material

    CN117229062A

  • High-thermal-conductivity epoxy resin composition based on copper-clad plate and preparation method of high-thermal-conductivity epoxy resin composition

    CN118725518A

  • Curable compositions

    US20160152819A1

  • Highly thermally conductive epoxy pouring sealant and preparation method therefor

    WO2021196513A1

Cited By

  • High-wear-resistance resin abrasive disc and preparation method thereof

    CN119952627A

  • Silica gel material and preparation method thereof

    CN120173281A